A Convenient Synthesis of Fluoroalkylated Benzimidazole‐ or Indole‐fused Benzoxazines. Issue 5 (3rd February 2022) - Hu, Yijie; Wang, Xiaoli; Ren, Nan; Li, Na; Li, Jianyang; Chen, Jie; Zhang, Hui; Deng, Hongmei; Cao, Weiguo; Lin, Jin‐Hong
Abstract: Fluoroalkyl group is of particular interest in pharmaceutical chemistry. Since benzimidazole‐ or indole‐fused benzoxazines are important motifs in numerous biologically active molecules, the incorporation of a fluoroalkyl group into these molecules may provide more opportunities for drug developments. Herein we describe the first synthesis of fluoroalkylated benzimidazole‐ or indole‐fused benzoxazines by using fluoroalkylated propiolates as building blocks. The reactions proceeded smoothly under mild conditions to give the desired products in moderate to high yields. Notably, benzimidazole‐fused products were obtained by a convenient one‐pot two‐step process. Abstract : Described herein is the first synthesis of fluoroalkylated benzimidazole‐ or indole‐fused benzoxazines by using fluoroalkylated propiolates as building blocks. The benzimidazole‐fused products were obtained by a convenient one‐pot two‐step process, a feature that may make this protocol attractive. The incorporation of a fluoroalkyl group into these heterocycles may provide more opportunities for drug developments.